2011
DOI: 10.5194/npg-18-791-2011
|View full text |Cite
|
Sign up to set email alerts
|

Frequency distributions: from the sun to the earth

Abstract: Abstract. The space environment is forever changing on all spatial and temporal scales. Energy releases are observed in numerous dynamic phenomena (e.g. solar flares, coronal mass ejections, solar energetic particle events) where measurements provide signatures of the dynamics. Parameters (e.g. peak count rate, total energy released, etc.) describing these phenomena are found to have frequency size distributions that follow power-law behavior. Natural phenomena on Earth, such as earthquakes and landslides, dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 94 publications
3
12
0
1
Order By: Relevance
“…The matching intervals of scales computed based on Equations (15) and (16) are shown by horizontal dash-dotted vertical lines in Figure 5 and vertical lines in Figure 7. It can be seen that the distributions decay algebraically, consistent with earlier observations of power-law statistics in solar photosphere and corona (Crosby et al 1993;Abramenko et al 2002;Aschwanden & Parnell 2002;Aschwanden 2011;Crosby 2011). The broadband power-law behavior of MDI distributions suggests that the dynamics of the LOS photospheric magnetic field is an inherently multiscale process (Uritsky & Davila 2012).…”
Section: Geometric and Probabilistic Scalingsupporting
confidence: 75%
See 1 more Smart Citation
“…The matching intervals of scales computed based on Equations (15) and (16) are shown by horizontal dash-dotted vertical lines in Figure 5 and vertical lines in Figure 7. It can be seen that the distributions decay algebraically, consistent with earlier observations of power-law statistics in solar photosphere and corona (Crosby et al 1993;Abramenko et al 2002;Aschwanden & Parnell 2002;Aschwanden 2011;Crosby 2011). The broadband power-law behavior of MDI distributions suggests that the dynamics of the LOS photospheric magnetic field is an inherently multiscale process (Uritsky & Davila 2012).…”
Section: Geometric and Probabilistic Scalingsupporting
confidence: 75%
“…SOC seeks to explain power-law distributions of flare parameters via cooperative interactions of a large number of nonlinearly coupled degrees of freedom representing unstable coronal loops and/or loop strands (Crosby et al 1993;Crosby 2011;Charbonneau et al 2001;Aschwanden et al 2000b;Aschwanden & Parnell 2002;Morales & Charbonneau 2008;Uritsky et al 2007). It has been suggested that the nonpotential magnetic field configurations existing in the corona release their free energy through a chain interaction of multiple spatially localized instabilities such as those associated with nanoflare heating (Parker 1988;Klimchuk 2006;Viall & Klimchuk 2011).…”
Section: Routes To Multiscale Dissipationmentioning
confidence: 99%
“…In accordance with numerous papers (see, for example, recent review by Crosby []), various events on the Sun and the Earth have similar shape of distributions: a top at small values, then a gentle slope and power law tail at large values. For instance, Tsubouchi and Omura [] showed that the distribution function of minimal D s t index for strong magnetic storms from 1957 to 2001 F ( D s t min ) has power law index γ ( F )∼−4.9.…”
Section: Introductionsupporting
confidence: 84%
“…Therefore, we also make a square approximation in log‐log space (see Table and thick lines in Figure ). The square law dependencies are too steeply decreasing, providing lower limits, and they do not agree with the conclusion about power law tails at large values [ Tsubouchi and Omura , ; Crosby , ; Riley , ]. We make two additional approximations for MC: (1) using the two last points ( γ ( P MC )∼−2.5, dash‐dotted line in Figure ) and (2) with fixed γ ( P MC )=−2.9 which gives us a waiting time T MC (−1700)∼1500 years, as calculated on the basis of F ∗ data (dashed line in Figure ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation